Pemahaman Akuntansi, Profesionalisme, dan Kinerja Pemeriksa Pajak pada Kpp Pratama Se-Bali - Ratna Sari, Maria Mediatrix; Suputra, Gde Dharma; Supadmi, Ni Luh (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
This study aims to improve the performance of tax inspectors in carrying out the inspection tasks, through understanding of financial accounting information  and  professionalism.  While  the  specific  purpose  of this study was to determine the effect of the  level of  understanding  of  financial  accounting  information and professionalism of the tax inspectors in the settlement of tax audits on KPP Pratama in Bali. Theories and concepts used in this study is the Minister of Finance Regulation No. 17 / PMK.03 / 2013 on Procedures for Tax Audit. The data analysis technique used in this study is the multiple linear regression, to test the quality of the data using validity and reliability, and classical assumption. The test results show that understanding of financial accounting information and professionalism affect the performance of tax inspectors. The higher level of financial  accounting information  understanding and  professionalism, then higher performance  of  tax  inspectors in the settlement  of  tax audits on KPP  Pratama in Bali.
Keywords: Pemahaman akuntansi, profesionalisme, kinerja pemeriksa pajak